1986
DOI: 10.1182/blood.v67.1.214.bloodjournal671214
|View full text |Cite
|
Sign up to set email alerts
|

Sulfhydryl reducing agents and shape regulation in human erythrocytes

Abstract: Metabolic crenation of red cells is reversible; on addition of nutrients, echinocytes recover the normal discoid shape. When the shape recovery takes place in the presence of reducing agents such as dithiothreitol (DTT), morphological change continues until the cells are stomatocytic. The degree of stomatocytosis varies, depending on the cell morphology when the nutrients and reducing agent are added. DTT has minimal effect on the shape of normal discocytes, but in its presence, mildly echinocytic cells become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It is generally believed that the biconcave disc shape of the erythrocyte is maintained by adenosine triphosphate (ATP) on the basis of observations made more than 5 decades ago on the disc‐sphere transformation of erythrocytes, via echinocytosis, induced by the glycolytic inhibitor sodium fluoride (NaF; 20 mmol·l –1 ) in a physiological saline or by storage of acid citric dextrose blood at 4 °C over a long period, and on the shape transformation of round ghost cells obtained from long‐stored erythrocytes after the addition of ATP . However, the process by which ATP depletion leads to the disc‐sphere transformation still remains unknown in spite of continuous investigations over the years in which the disc‐sphere transformation was generally induced by glucose depletion in buffered saline . Indeed, it appears unrelated to any of the following: (i) active transport of Na + and K + by ouabain‐sensitive membrane Na + , K + ‐ATPase, opposed by Na + and K + leakage; (ii) Ca 2+ uptake, opposed by membrane Ca 2+ ‐ATPase; (iii) formation of lysophosphatidylcholine by a fatty acid deacylation of phosphatidylcholine, opposed by a ATP‐dependent fatty acid acylation; (iv) phosphorylation state of long and flexible filamentous spectrin, constituting 60% of the total proteins of the two‐dimensional reticulated membrane skeleton; (v) phosphorylation state of the major transmembrane protein Band 3 (AE1), exchanging anion chloride (Cl – ), and bicarbonate (HCO 3 – ) and binding to filamentous spectrin near its center by intermediary of ankyrin R; (vi) metabolism of phosphatidylinositides, constituting 1–2% of the total membrane phospholipids; (vii) contraction of the erythrocyte by myosin present at a relatively low cell number copies (~6000), presumably interacting with actin protofilament cross‐linking spectrin at its ends with Band 4.1R binding to glycophorin C .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It is generally believed that the biconcave disc shape of the erythrocyte is maintained by adenosine triphosphate (ATP) on the basis of observations made more than 5 decades ago on the disc‐sphere transformation of erythrocytes, via echinocytosis, induced by the glycolytic inhibitor sodium fluoride (NaF; 20 mmol·l –1 ) in a physiological saline or by storage of acid citric dextrose blood at 4 °C over a long period, and on the shape transformation of round ghost cells obtained from long‐stored erythrocytes after the addition of ATP . However, the process by which ATP depletion leads to the disc‐sphere transformation still remains unknown in spite of continuous investigations over the years in which the disc‐sphere transformation was generally induced by glucose depletion in buffered saline . Indeed, it appears unrelated to any of the following: (i) active transport of Na + and K + by ouabain‐sensitive membrane Na + , K + ‐ATPase, opposed by Na + and K + leakage; (ii) Ca 2+ uptake, opposed by membrane Ca 2+ ‐ATPase; (iii) formation of lysophosphatidylcholine by a fatty acid deacylation of phosphatidylcholine, opposed by a ATP‐dependent fatty acid acylation; (iv) phosphorylation state of long and flexible filamentous spectrin, constituting 60% of the total proteins of the two‐dimensional reticulated membrane skeleton; (v) phosphorylation state of the major transmembrane protein Band 3 (AE1), exchanging anion chloride (Cl – ), and bicarbonate (HCO 3 – ) and binding to filamentous spectrin near its center by intermediary of ankyrin R; (vi) metabolism of phosphatidylinositides, constituting 1–2% of the total membrane phospholipids; (vii) contraction of the erythrocyte by myosin present at a relatively low cell number copies (~6000), presumably interacting with actin protofilament cross‐linking spectrin at its ends with Band 4.1R binding to glycophorin C .…”
mentioning
confidence: 99%
“…Indeed, it appears unrelated to any of the following: (i) active transport of Na + and K + by ouabain‐sensitive membrane Na + , K + ‐ATPase, opposed by Na + and K + leakage; (ii) Ca 2+ uptake, opposed by membrane Ca 2+ ‐ATPase; (iii) formation of lysophosphatidylcholine by a fatty acid deacylation of phosphatidylcholine, opposed by a ATP‐dependent fatty acid acylation; (iv) phosphorylation state of long and flexible filamentous spectrin, constituting 60% of the total proteins of the two‐dimensional reticulated membrane skeleton; (v) phosphorylation state of the major transmembrane protein Band 3 (AE1), exchanging anion chloride (Cl – ), and bicarbonate (HCO 3 – ) and binding to filamentous spectrin near its center by intermediary of ankyrin R; (vi) metabolism of phosphatidylinositides, constituting 1–2% of the total membrane phospholipids; (vii) contraction of the erythrocyte by myosin present at a relatively low cell number copies (~6000), presumably interacting with actin protofilament cross‐linking spectrin at its ends with Band 4.1R binding to glycophorin C . Moreover, there are several observations suggesting that ATP is not the only determinant of the erythrocyte shape . It has been previously suggested that inorganic phosphate (P i ) also is a determinant of the erythrocyte shape .…”
mentioning
confidence: 99%
See 3 more Smart Citations